1991
DOI: 10.1073/pnas.88.15.6523
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelial-leukocyte adhesion molecule 1 (ELAM-1) gene transcription.

Abstract: Leukocyte adherence to endothelium is in part mediated by the transient expression of endothelialleukocyte adhesion molecule 1 (ELAM-1) on endothelial surfaces stimulated by tumor necrosis factor a (TNF), interleukin (IL) 1, or bacterial lipopolysaccharide (LPS). The intracellular factors controlling induction of ELAM-1 mRNA and protein are unknown. In nuclear runoff experiments with cultured human umbilical vein endothelial cells (HUVEC), we demonstrate that transcriptional activation of the ELAM-1 gene occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
1
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(131 citation statements)
references
References 40 publications
8
120
1
2
Order By: Relevance
“…Factors commonly found in inflammatory atherogenic lesions, such as the cytokines TNFa and IL-1A, induce the concurrent expression of VCAM-1, ICAM-1, and E-selectin in cultured endothelial cells (see reference 2 for review). This same pattern of expression is observed in culture with other agents such as bacterial endotoxin LPS and the synthetic double-stranded RNA, polyinosinic:polycitidylic acid, poly(I:C) (PIC) (12)(13)(14). Clearly, these factors alone cannot selectively activate VCAM-1 gene expression and this raises the issue of whether these factors activate VCAM-1, ICAM-1, and E-selectin expression through a common, or gene-specific, molecular regulatory pathway.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Factors commonly found in inflammatory atherogenic lesions, such as the cytokines TNFa and IL-1A, induce the concurrent expression of VCAM-1, ICAM-1, and E-selectin in cultured endothelial cells (see reference 2 for review). This same pattern of expression is observed in culture with other agents such as bacterial endotoxin LPS and the synthetic double-stranded RNA, polyinosinic:polycitidylic acid, poly(I:C) (PIC) (12)(13)(14). Clearly, these factors alone cannot selectively activate VCAM-1 gene expression and this raises the issue of whether these factors activate VCAM-1, ICAM-1, and E-selectin expression through a common, or gene-specific, molecular regulatory pathway.…”
Section: Introductionmentioning
confidence: 65%
“…4, VCAM-1 'ar 0.050~_ Fig. 6, PDTC had no effect on pSV2CAT activity (duplicate experiments, lanes [11][12][13][14] suggesting that the mechanism by which PDTC blocks VCAM-1 promoter activation is not due to a (37) and ICAM-1 (38).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent findings also show that BRAP can influence NF-B nucleus translocation, leading to an increase of proinflammatory molecules (unpublished data). In addition, previous studies [27][28][29][30][31][32][33] demonstrated that NF-B can regulate a number of inflammatory genes, including interleukin-6 (IL-6), tumor necrosis factor (TNF), vascular cellular adhesion molecule-1 (VCAM-1), E-selectin, inducible nitric oxide synthase (iNOS), matrix metallo-proteinases (MMPs) and CRP. BRAP was originally identified as a cytoplasmic protein that recognizes the nuclear localization signal of the breast cancer suppressor protein, BRCA-1 1,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention has been paid to members of the c-rel family of transcription factors in the regulation of genes involved in the inflammatory response. Functional analysis of the promoters of the GM-CSF [18], tissue factor [19], M-CSF [20], IL-6 [21], E-selectin [22,23], ICAM-1 [24] and VCAM-1 [ 13,16,17] genes have demonstrated that NF-kB-binding sites are essential for the transcriptional regulation of these inflammatory mediators in endothelium, lymphocytes and monocytes. In contrast, little is known about the promoter elements required for IL-4-induced VCAM-1 expression.…”
Section: Introductionmentioning
confidence: 99%